Polyacrylate composite pressure-sensitive adhesive, transdermal patch and preparation method

By blending itaconic acid and inorganic nanoparticles in the polyacrylate pressure-sensitive adhesive, the polyacrylate composite pressure-sensitive adhesive is solved, and the problems of poor adhesion and water resistance of traditional patches are significantly improved, which enhances the adhesion and water resistance and enhances the clinical application performance.

CN119570406AInactive Publication Date: 2025-03-07YANBIAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510143554.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional transdermal patches have problems with poor matrix adhesion and poor water resistance, which leads to poor clinical application performance.

Method used

Polyacrylate composite pressure-sensitive adhesives are used, which include polyacrylate pressure-sensitive adhesives, itaconic acid and inorganic nanoparticles, and specifically spherical mesoporous titanium dioxide nanoparticles and carboxylated spherical mesoporous titanium dioxide nanoparticles.

Benefits of technology

It significantly improves the bonding performance, water resistance and antibacterial properties of pressure-sensitive adhesives, enhances adhesion to the skin surface, and improves the clinical application performance of the patch.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570406A_ABST
    Figure CN119570406A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pressure-sensitive adhesives, and particularly relates to a polyacrylate composite pressure-sensitive adhesive, a transdermal patch and a preparation method. The polyacrylate composite pressure-sensitive adhesive disclosed by the invention is obtained by blending itaconic acid and inorganic nanoparticles in a polyacrylate pressure-sensitive adhesive. The itaconic acid and the inorganic nanoparticles are jointly used as a cross-linking agent, so that the material not only has the advantages of high rigidity and the like of an inorganic material, but also has the advantage of high viscoelasticity of a polymer material, and the defects of poor substrate adhesion and poor water resistance of a traditional patch are effectively overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressure-sensitive adhesives, and in particular relates to a polyacrylate composite pressure-sensitive adhesive, a transdermal patch and a preparation method thereof. Background Art

[0002] Transdermal drug delivery system has aroused great interest in the pharmaceutical industry since its emergence in the 1980s. Transdermal drug delivery system is a new way of non-invasive drug delivery and the latest drug dosage form in the world. Its advantages are mainly as follows: ① It can produce lasting, constant and controllable blood drug concentration, thereby reducing adverse reactions; ② Avoid the first-pass effect of the liver and improve the bioavailability of drugs; ③ Reduce the pain of injection and improve patient compliance; ④ Patients can take the medicine by themselves and stop the medicine in time if there is a problem, which is convenient to use; ⑤ Reduce the number of administrations and dosages, and have good application prospects.

[0003] At present, the dosage form of transdermal drug delivery system is mainly transdermal patch, and its structure mainly includes backing layer, adhesive and release film. Among them, pressure-sensitive adhesive is the main excipient in transdermal patch, which can make the drug delivery system fit closely with the skin, and can also be used as a carrier of drugs to regulate drug release. However, traditional transdermal patches generally have problems of poor matrix adhesion and poor water resistance, which leads to unsatisfactory clinical application performance. Summary of the invention

[0004] To this end, the object of the present invention is to provide a polyacrylate composite pressure-sensitive adhesive to solve the problems of poor adhesion and poor water resistance of traditional patch matrices in the prior art; The second object of the present invention is to provide a transdermal patch with better adhesion and water resistance; The third object of the present invention is to provide a method for preparing the polyacrylate composite pressure-sensitive adhesive and transdermal patch.

[0005] In order to solve the above technical problems, the polyacrylate composite pressure-sensitive adhesive of the present invention comprises a polyacrylate pressure-sensitive adhesive, and a mixture of itaconic acid and inorganic nanoparticles; The inorganic nanoparticles include spherical mesoporous titanium dioxide nanoparticles and / or carboxylated spherical mesoporous titanium dioxide nanoparticles; The addition amount of itaconic acid based on the polyacrylate pressure-sensitive adhesive is 0.1-0.5wt%; The inorganic nanoparticles are added in an amount of 0.1-1.0 wt % based on the polyacrylate pressure-sensitive adhesive.

[0006] Specifically, the polyacrylate composite pressure-sensitive adhesive: The inorganic nanoparticles include spherical mesoporous titanium dioxide nanoparticles; the spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5wt% based on the polyacrylate pressure-sensitive adhesive; or, The inorganic nanoparticles include carboxylated spherical mesoporous titanium dioxide nanoparticles; the carboxylated spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5wt% based on the polyacrylate pressure-sensitive adhesive; or, The inorganic nanoparticles include a mixture of spherical mesoporous titanium dioxide nanoparticles and carboxylated spherical mesoporous titanium dioxide nanoparticles; the addition amount of the spherical mesoporous titanium dioxide nanoparticles based on the polyacrylate pressure-sensitive adhesive is 0.1-0.5wt%; the addition amount of the carboxylated spherical mesoporous titanium dioxide nanoparticles based on the polyacrylate pressure-sensitive adhesive is 0.1-0.5wt%.

[0007] Specifically, the parameters of the polyacrylate composite pressure-sensitive adhesive and the spherical mesoporous titanium dioxide nanoparticles include: a specific surface area of ​​200-300 m 2 g -1 , average pore size 7-8nm, average pore volume size 0.4-0.5cm 3 g -1 ; Preferably, the preparation method of the spherical mesoporous titanium dioxide nanoparticles comprises: Tetrabutyl titanate is added to ethylene glycol and mixed, and a mixed solution of acetone and water is added to mix, and the precipitate is collected to obtain ethylene glycol titanium; The titanium glycolate is collected, water is added, and the mixture is heated and refluxed to obtain the desired spherical mesoporous titanium dioxide nanoparticles.

[0008] The preferred heating reflux temperature is 100-120° C., and the preferred heating reflux time is 1-2 h.

[0009] Specifically, the parameters of the polyacrylate composite pressure-sensitive adhesive and the carboxylated spherical mesoporous titanium dioxide nanoparticles include: a specific surface area of ​​180-220 m 2 .g -1 , average pore size 4.5-5.0nm, average pore volume size 0.2-0.3cm 3 g -1 ; Preferably, the preparation method of the carboxylated spherical mesoporous titanium dioxide nanoparticles comprises: taking TiO2 powder, adding alkali solution, mixing, and adding sodium chloroacetate to heat and react; collecting the reactants and washing them until they are neutral, thereby obtaining; Preferably, the alkali solution comprises NaOH solution; Preferably, the temperature of the heating reaction is 100-120°C.

[0010] Specifically, the polyacrylate composite pressure-sensitive adhesive comprises the following components in parts by weight: Soft monomer 55-70 parts by weight; 30-40 parts by weight of hard monomer; Functional monomer 0-5 parts by weight; Initiator 0.3-0.8 parts by weight; 80-120 parts by weight of solvent.

[0011] In the above-mentioned pressure-sensitive adhesive system, the amount of initiator added is 0.3-0.8 parts by weight. The lower limit amount of the initiator within this range can initiate the polymerization reaction to a certain extent. At this amount, for some monomer systems with higher activity or under relatively mild reaction conditions (such as appropriate temperature, pressure, etc.), it is sufficient to produce enough free radicals to start the polymerization reaction, so that the monomers are gradually polymerized to form polymers. At the same time, a lower amount of initiator helps to control the reaction rate and avoid the polymerization process being difficult to control due to excessive reaction. For example, excessive heat may cause problems such as implosion, which affects the performance and quality of the pressure-sensitive adhesive. The upper limit amount of the initiator within this range can ensure that under various possible reaction conditions (such as low monomer activity, certain impurities in the reaction system, etc. that may affect the initiation efficiency), there are enough initiators to provide enough free radicals to ensure that the polymerization reaction can proceed smoothly to a higher conversion rate. At the same time, it also effectively avoids some problems that may be caused by excessive initiator dosage, such as the increase of byproducts produced by the decomposition of the initiator itself, which may remain in the pressure-sensitive adhesive system, affecting the performance of the pressure-sensitive adhesive, such as reducing its stability, bonding performance or biocompatibility.

[0012] In the above-mentioned pressure-sensitive adhesive system, the amount of solvent is 80-120 parts by weight, and the lower limit amount of solvent in this range can provide enough fluidity for the polymerization reaction system, so that the monomer can be fully mixed and uniform, which is conducive to the initiator being evenly dispersed in the system, thereby ensuring that the polymerization reaction is uniformly carried out in the whole system. At the same time, an appropriate amount of solvent helps to control the viscosity of the reaction system, avoids the problems such as heat dissipation difficulty and molecular chain motion limitation caused by excessive viscosity, and affects the normal progress of the polymerization reaction. In addition, a certain amount of solvent is also necessary for dissolving monomers and polymers, ensuring that the reaction system is a homogeneous system, which is conducive to the smooth progress of the reaction. And the upper limit amount of solvent in this range mainly considers the effect of the solvent in the reaction process and the convenience of subsequent processing. At the same time, more solvents can further reduce the viscosity of the system, facilitate stirring, heat transfer and other operations during the polymerization reaction, and contribute to the stable progress of the reaction, especially for some high-concentration monomer systems or in large-scale production, appropriately increasing the amount of solvent can improve the operability of the reaction. At the same time, it can avoid a series of problems caused by excessive solvent usage, such as requiring more energy and time to remove the solvent after the polymerization reaction is completed, increasing production costs; and the presence of a large amount of solvent may affect the final structure and properties of the polymer, such as increasing the distance between polymer molecular chains, affecting the cohesion and bonding properties of the pressure-sensitive adhesive, etc.

[0013] Specifically, the polyacrylate composite pressure-sensitive adhesive: The soft monomer comprises a monomer having a glass transition temperature (Tg) of -5°C to 120°C, preferably at least one of isooctyl acrylate, 2-ethylhexyl acrylate or n-butyl acrylate; and / or, The hard monomer includes at least one of methyl acrylate, ethyl acrylate, methyl methacrylate or ethyl methacrylate; and / or, The functional monomer includes at least one of hydroxyethyl acrylate and acrylic acid; and / or, The initiator comprises benzoyl peroxide; and / or, The solvent included ethyl acetate.

[0014] The present invention also discloses a method for preparing the polyacrylate composite pressure-sensitive adhesive, comprising the steps of blending a selected amount of the polyacrylate pressure-sensitive adhesive with itaconic acid and inorganic nanoparticles; Preferably, the blending step includes a step of stirring at a rate of 300-500 r / min.

[0015] Specifically, the method for preparing the polyacrylate composite pressure-sensitive adhesive further includes the step of preparing the polyacrylate pressure-sensitive adhesive, including the step of mixing selected amounts of the soft monomer, hard monomer, functional monomer, initiator and solvent, and performing a polymerization reaction under a protective atmosphere; Preferably, the polymerization reaction temperature is 75-85°C; Preferably, the mixing step includes a stirring step at 100-150 r / min.

[0016] The invention also discloses the use of the polyacrylate composite pressure-sensitive adhesive in preparing transdermal patches, especially transdermal patch drug-carrying materials.

[0017] The present invention also discloses a transdermal patch, comprising a backing layer, a drug-carrying layer and an anti-adhesive layer; The drug-carrying layer comprises a mixture of the polyacrylate composite pressure-sensitive adhesive and an active drug; Preferably, the active drug accounts for 1-3wt% of the mass of the polyacrylate composite pressure-sensitive adhesive; Preferably, the active drug comprises at least one of ketoprofen, indomethacin, diclofenac or lidocaine.

[0018] The present invention also discloses a method for preparing the transdermal patch, comprising the following steps: Taking a selected amount of the polyacrylate composite pressure-sensitive adhesive and mixing it with an active drug; Placing the obtained mixture on the selected anti-sticking layer surface and curing it to form the drug-carrying layer; The selected backing layer is compounded to obtain; Preferably, the curing step comprises the step of standing at 20-30°C for 0.5-1.5 hours, and the step of drying at 45-55°C and standing for 10-20 minutes.

[0019] The polyacrylate composite pressure-sensitive adhesive of the present invention is obtained by mixing itaconic acid and inorganic nanoparticles in the polyacrylate pressure-sensitive adhesive. The itaconic acid and the inorganic nanoparticles are used together as a cross-linking agent, so that the material has the advantages of high rigidity of inorganic materials and the advantages of high viscoelasticity of polymer materials. In particular, the added itaconic acid can be used as a biomass acid to have anti-inflammatory, antioxidant and antibacterial effects, and can exert an antibacterial effect by inhibiting the activity of bacterial isocitrate lyase (ICL), effectively improving the antibacterial performance of the polyacrylate composite pressure-sensitive adhesive and improving clinical application performance.

[0020] The polyacrylate composite pressure-sensitive adhesive of the present invention selects inorganic nanoparticles as spherical mesoporous titanium dioxide nanoparticles and / or carboxylated spherical mesoporous titanium dioxide nanoparticles, and utilizes the advantages of spherical mesoporous titanium dioxide having no physiological toxicity, uniform pore size, large specific surface area, easy surface modification, stable chemical properties and good biocompatibility, and is incorporated into the pressure-sensitive adhesive, and the hydroxyl groups on its surface can interact with the molecules between the polymer chains, and the crosslinking degree of the pressure-sensitive adhesive can be improved, especially during the crosslinking process, the polymer system can form a network structure, which can significantly increase the molecular weight, thereby improving the cohesion of the system, resulting in a significant increase in the holding force, thereby enhancing the adhesion to the skin surface. The roughness of the surface of the carboxy-modified mesoporous TiO2 sphere is reduced, and the agglomeration between the spheres is reduced, the dispersibility is better, and the particle size is relatively reduced, which is conducive to subsequent combination with the polymer. The polyacrylate composite pressure-sensitive adhesive system of the present invention effectively improves the bonding performance of the pressure-sensitive adhesive, enhances the adhesion to the skin tissue, and significantly enhances the water resistance of the pressure-sensitive adhesive. In the polyacrylate composite pressure-sensitive adhesive of the present invention, the added spherical mesoporous titanium dioxide nanoparticles and carboxylated spherical mesoporous titanium dioxide nanoparticles can be prepared by a hydrothermal synthesis method, and have the advantage of simple processing.

[0021] In the polyacrylate composite pressure-sensitive adhesive of the present invention, the polyacrylate pressure-sensitive adhesive can be obtained by conventional free radical polymerization methods in the art, such as polymerization based on soft monomers, hard monomers, functional monomers and initiators, and also has the advantages of wide sources and simple processing methods.

[0022] The transdermal patch of the present invention is based on the polyacrylate composite pressure-sensitive adhesive as a drug-carrying material, which can be used as a drug-carrying layer of the transdermal patch after being mixed with an active drug and cured. The polyacrylate composite pressure-sensitive adhesive has the advantages of high bonding performance, good water resistance, high peel strength, low water absorption, high air permeability, etc., which effectively solves the shortcomings of poor adhesion and poor water resistance of traditional patch matrix. The transdermal patch of the present invention can release 42% of active drugs such as ketoprofen within 3 days, has good release performance effect, and is more effective in clinical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 FTIR spectra of pressure-sensitive adhesives with different IA contents added; Figure 2 FTIR spectra of pressure sensitive adhesives with different TiO2 contents; Figure 3 FTIR spectra of pressure sensitive adhesives with different COOH-TiO2 contents; Figure 4The effect of different IA contents on the pressure-sensitive adhesive before and after immersion in water; (a) is the initial adhesion, (b) is the sustained adhesion, and (c) is the 180° peel strength; in each group of bar graphs, the left side is before immersion in water, and the right side is after immersion in water; Figure 5 The effect of different contents of spherical mesoporous titanium dioxide (TiO2) on the pressure-sensitive adhesive before and after immersion in water; (a) is the initial adhesion, (b) is the sustained adhesion, and (c) is the 180° peel strength; in each group of bar graphs, the left side is before immersion in water, and the right side is after immersion in water; Figure 6 The effect of different contents of carboxylated spherical mesoporous titanium dioxide (COOH-TiO2) on the pressure-sensitive adhesive before and after immersion in water; (a) is the initial adhesion, (b) is the sustained adhesion, and (c) is the 180° peel strength; in each group of bar graphs, the left side is before immersion in water, and the right side is after immersion in water; Figure 7 The effects of different contents of IA, TiO2, and COOH-TiO2 on the water absorption of pressure-sensitive adhesives; Figure 8 The effects of different contents of IA, TiO2, and COOH-TiO2 on the water vapor transmission rate of pressure-sensitive adhesives; Fig. 9 The in vitro release percentage curves of different patches. DETAILED DESCRIPTION

[0024] In the following embodiments of the present invention, itaconic acid and inorganic nanoparticles are mixed into a polyacrylate pressure-sensitive adhesive to form a composite pressure-sensitive adhesive.

[0025] Specifically, the inorganic nanoparticles include spherical mesoporous titanium dioxide nanoparticles and / or carboxylated spherical mesoporous titanium dioxide nanoparticles.

[0026] In some embodiments, the itaconic acid is added in an amount of 0.1-0.5 wt % based on the polyacrylate pressure-sensitive adhesive.

[0027] In some embodiments, the inorganic nanoparticles are added in an amount of 0.1-1.0 wt % based on the polyacrylate pressure-sensitive adhesive.

[0028] In some embodiments, the inorganic nanoparticles include spherical mesoporous titanium dioxide nanoparticles; preferably, the spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5 wt % based on the polyacrylate pressure-sensitive adhesive.

[0029] In some embodiments, the inorganic nanoparticles include carboxylated spherical mesoporous titanium dioxide nanoparticles; preferably, the added amount of the carboxylated spherical mesoporous titanium dioxide nanoparticles is 0.1-0.5 wt % based on the polyacrylate pressure-sensitive adhesive.

[0030] In some embodiments, the inorganic nanoparticles include a mixture of spherical mesoporous titanium dioxide nanoparticles and carboxylated spherical mesoporous titanium dioxide nanoparticles; preferably, the spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5wt% based on the polyacrylate pressure-sensitive adhesive; preferably, the carboxylated spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5wt% based on the polyacrylate pressure-sensitive adhesive.

[0031] In the following examples of the present invention, the spherical mesoporous titanium dioxide nanoparticles are prepared by hydrothermal synthesis. As an exemplary embodiment, the preparation method of the spherical mesoporous titanium dioxide nanoparticles includes: adding tetrabutyl titanate to ethylene glycol, mixing, adding a mixed solution of acetone and water, collecting the precipitate to obtain ethylene glycol titanium; and collecting the ethylene glycol titanium, adding water, heating and refluxing, and obtaining the desired spherical mesoporous titanium dioxide nanoparticles.

[0032] In some embodiments, in the hydrothermal synthesis method, the temperature of the heating reflux treatment is 100-120° C., and the treatment time is 1-2 hours.

[0033] In some embodiments, in the hydrothermal synthesis method, the ratio between the various materials can be selected according to conventional means in the art. For example, in some embodiments, the volume ratio of the tetrabutyl titanate to the ethylene glycol can be adjusted to 1-3:40-60, which can ensure that the mixed system of the two is uniform. For example, in some embodiments, the volume ratio of the tetrabutyl titanate to the acetone and water can be adjusted to 1-3:150-180:2-3, which can ensure the stable reaction of the entire hydrothermal synthesis system, thereby obtaining spherical mesoporous titanium dioxide nanoparticles with desired properties.

[0034] In some embodiments, in the hydrothermal synthesis method, the mass ratio of titanium glycolate to water is 1:150-250, which can ensure the smooth progress of the hydrothermal synthesis process.

[0035] In some embodiments, in the hydrothermal synthesis method, the collected titanium glycolate precipitate is washed sufficiently and then dried at 60-100° C., for example, for 6-10 hours.

[0036] In some embodiments, in the hydrothermal synthesis method, the reactants after heating and reflux treatment are filtered to collect the precipitate, washed sufficiently, and then dried at 60-100° C., for example, for 6-10 hours.

[0037] In the following examples of the present invention, the carboxylated spherical mesoporous titanium dioxide nanoparticles are prepared by hydrothermal synthesis. As an exemplary embodiment, the preparation method of the carboxylated spherical mesoporous titanium dioxide nanoparticles includes: taking TiO2 powder, adding alkaline solution, mixing, and adding sodium chloroacetate for heating reaction; collecting the reactants and washing them until neutral, thereby obtaining.

[0038] In some embodiments, in the hydrothermal synthesis method, the ratio of each material can be selected according to conventional means in the art. For example, in some embodiments, adjusting the molar ratio of the TiO2 to the sodium chloroacetate to 1-1.5:1 can ensure the stable reaction of the entire hydrothermal synthesis system, thereby obtaining carboxylated spherical mesoporous titanium dioxide nanoparticles with desired properties.

[0039] In some embodiments, the alkali solution illustratively includes a NaOH solution.

[0040] In some embodiments, the temperature of the heating reaction is illustratively 100-120°C.

[0041] In some embodiments, in the hydrothermal synthesis method, TiO2 powder is added to an alkali solution and then ultrasonically treated and suspended, for example, ultrasonically treated for 30-60 minutes.

[0042] In some embodiments, in the hydrothermal synthesis method, the collected reactants are washed to neutrality and then separated from the carboxylated TiO2 particles at a rotation speed of 3000-5000 r / min.

[0043] In some embodiments, in the hydrothermal synthesis method, the separated carboxylated TiO2 particles are fully dried at 60-100°C.

[0044] In the following embodiments of the present invention, the polyacrylate pressure-sensitive adhesive may be a commercially available polyacrylate pressure-sensitive adhesive product of the prior art, or may be chemically synthesized according to methods known in the art, such as emulsion polymerization.

[0045] As an exemplary embodiment, in the following examples of the present invention, the polyacrylate pressure-sensitive adhesive includes the following components in parts by weight: 55-70 parts by weight of soft monomer, 30-40 parts by weight of hard monomer, 0-5 parts by weight of functional monomer, 0.3-0.8 parts by weight of initiator, and 80-120 parts by weight of solvent.

[0046] In some embodiments, the soft monomer includes isooctyl acrylate.

[0047] In some embodiments, the hard monomer includes methyl acrylate.

[0048] In some embodiments, the functional monomer includes hydroxyethyl acrylate.

[0049] In some embodiments, the initiator comprises benzoyl peroxide.

[0050] In some embodiments, the solvent comprises ethyl acetate.

[0051] In some specific embodiments, the polyacrylate pressure-sensitive adhesive can be synthesized by free radical polymerization, for example, selected amounts of the soft monomer, hard monomer, functional monomer, initiator and solvent are mixed and polymerization is carried out under a protective atmosphere.

[0052] In some embodiments, the polymerization reaction temperature is 75-85°C; In some specific embodiments, the mixing step includes a stirring step at 100-150 r / min.

[0053] In some specific embodiments, a certain amount of solvent such as ethyl acetate may be added to dilute the obtained pressure-sensitive adhesive according to its viscosity, stirred evenly, and cooled to room temperature.

[0054] The present invention can be better understood according to the following embodiments. The technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0055] Preparation Example 1 In this preparation example, a hydrothermal synthesis method is used to prepare the desired spherical mesoporous titanium dioxide nanoparticles (denoted as TiO2).

[0056] Accurately measure 2.000mL of tetrabutyl titanate, add 50.000mL of ethylene glycol, stir the mixed solution at room temperature for 8h, then add the mixed solution to a mixed solution containing 170.000mL of acetone and 2.700mL of deionized water, and stir at room temperature for 1h. After the reaction is completed, collect the white precipitate, wash it by repeated centrifugation for 5 times, and dry it at 80℃ for 8h to obtain ethylene glycol titanium powder.

[0057] Take 0.100g of the titanium glycolate prepared above, add 20.000mL of water and mix, heat under reflux at 100°C for 1h, collect the obtained white precipitate, wash it by repeated centrifugation for 5 times, and dry it at 80°C for 8h to obtain the desired spherical mesoporous titanium dioxide nanoparticles.

[0058] The specific surface area of ​​the spherical mesoporous titanium dioxide nanoparticles described in this preparation example is 250 m 2 g -1 The average pore size is 7.6nm and the average pore volume is 0.47cm 3 g-1 .

[0059] Preparation Example 2 In this preparation example, a hydrothermal synthesis method is used to prepare the desired spherical mesoporous titanium dioxide nanoparticles (denoted as TiO2).

[0060] Accurately measure 1.000mL of tetrabutyl titanate, add 60.000mL of ethylene glycol, stir the mixed solution at room temperature for 6h, then add the mixed solution to a mixed solution containing 150.000mL of acetone and 3.000mL of deionized water, and stir at room temperature for 1h. After the reaction is completed, collect the white precipitate, wash it by repeated centrifugation for 5 times, and dry it at 60℃ for 10h to obtain ethylene glycol titanium powder.

[0061] Take 0.100g of the titanium glycol prepared above, add 15.000mL of water and mix, heat and reflux at 110°C for 1h, collect the obtained white precipitate, wash it by repeated centrifugation for 5 times, and dry it at 60°C for 10h to obtain the desired spherical mesoporous titanium dioxide nanoparticles.

[0062] Preparation Example 3 In this preparation example, a hydrothermal synthesis method is used to prepare the desired spherical mesoporous titanium dioxide nanoparticles (denoted as TiO2).

[0063] Accurately measure 3.000mL of tetrabutyl titanate, add 40.000mL of ethylene glycol, stir the mixed solution at room temperature for 10h, then add the mixed solution to a mixed solution containing 180.000mL of acetone and 2.000mL of deionized water, and stir at room temperature for 1h. After the reaction is completed, collect the white precipitate, wash it by repeated centrifugation for 5 times, and dry it at 100℃ for 6h to obtain ethylene glycol titanium powder.

[0064] Take 0.100g of the titanium glycol prepared above, add 25.000mL of water and mix, heat and reflux at 120°C for 2h, collect the obtained white precipitate, wash it by repeated centrifugation for 5 times, and dry it at 100°C for 6h to obtain the desired spherical mesoporous titanium dioxide nanoparticles.

[0065] Preparation Example 4 In this preparation example, a hydrothermal synthesis method is used to prepare the desired carboxylated spherical mesoporous titanium dioxide nanoparticles (denoted as COOH-TiO2).

[0066] Accurately weigh 2.333g TiO2 powder and 30.000mL 1mol / L NaOH solution under magnetic stirring, add to 300.000mL deionized water, stir the suspension at room temperature for 1h, and ultrasonically treat the suspension for 30min. Then, add 2.920g sodium chloroacetate to the suspension, stir the mixed solution at 110℃ for 4h, remove the upper liquid after the mixed solution is cooled to room temperature, and wash repeatedly with deionized water until the pH value of the solution becomes neutral. Finally, separate the carboxylated TiO2 particles in a centrifuge at a speed of 4000 r / min for 30min, and dry them in an oven at 80℃ overnight to obtain carboxylated mesoporous titanium dioxide nanoparticles.

[0067] The specific surface area of ​​the carboxylated mesoporous titanium dioxide nanoparticles described in this preparation example is 201 m 2 .g -1 The average pore size is 4.8 nm and the average pore volume is 0.24 cm 3 g -1 .

[0068] Preparation Example 5 In this preparation example, a hydrothermal synthesis method is used to prepare the desired carboxylated spherical mesoporous titanium dioxide nanoparticles (denoted as COOH-TiO2).

[0069] Accurately weigh 2.000g TiO2 powder and 30.000mL 1mol / L NaOH solution, add to 300.000mL deionized water under magnetic stirring, stir the suspension at room temperature for 1h, and ultrasonically treat the suspension for 60min. Then, add 2.920g sodium chloroacetate to the suspension, stir the mixed solution at 100℃ for 5h, remove the upper liquid after the mixed solution is cooled to room temperature, and wash repeatedly with deionized water until the pH value of the solution becomes neutral. Finally, separate the carboxylated TiO2 particles in a centrifuge at a speed of 3000r / min for 40min, and dry them in an oven at 60℃ overnight to obtain carboxylated mesoporous titanium dioxide nanoparticles.

[0070] Preparation Example 6 In this preparation example, a hydrothermal synthesis method is used to prepare the desired carboxylated spherical mesoporous titanium dioxide nanoparticles (denoted as COOH-TiO2).

[0071] Accurately weigh 3.600g TiO2 powder and 30.000mL 1mol / L NaOH solution, add to 300mL deionized water under magnetic stirring, stir the suspension at room temperature for 1h, and ultrasonically treat the suspension for 40min. Then, add 2.920g sodium chloroacetate to the suspension, and stir the mixed solution at 120℃ for 3h. After the mixed solution is cooled to room temperature, remove the upper liquid and wash repeatedly with deionized water until the pH value of the solution becomes neutral. Finally, separate the carboxylated TiO2 particles in a centrifuge at a speed of 5000r / min for 20min, and dry them in an oven at 100℃ overnight to obtain carboxylated mesoporous titanium dioxide nanoparticles.

[0072] Preparation Example 7 In this preparation example, a free radical polymerization method is used to synthesize a polyacrylate pressure-sensitive adhesive.

[0073] Take 60.000g of isooctyl acrylate (2-EHA), 35.000g of methyl acrylate (MA), 3.000g of hydroxyethyl acrylate (HEA), and 800.000g of ethyl acetate (EA) respectively, and add them into a four-necked flask in order according to the mass ratio. Install a condensation reflux device, a stirring device and a nitrogen blowing device on the four-necked flask, heat it in a water bath at 75°C, and stir it continuously at 100 r / min; continue to add 0.300g of initiator benzoyl peroxide (BPO) and mix it evenly. Under nitrogen protection, the reaction time lasts for 10 hours to remove the residual monomer as much as possible. Stop the reaction, turn off the water bath and nitrogen, and collect the reactants to obtain.

[0074] Preparation Example 8 In this preparation example, a free radical polymerization method is used to synthesize a polyacrylate pressure-sensitive adhesive.

[0075] Take 55.000g of isooctyl acrylate (2-EHA), 40.000g of methyl acrylate (MA), 5.000g of hydroxyethyl acrylate (HEA), and 100.000g of ethyl acetate (EA) respectively, and add them into a four-necked flask in order according to the mass ratio. Install a condensation reflux device, a stirring device, and a nitrogen blowing device on the four-necked flask, heat it in a water bath at 80°C, and continue stirring at 120 r / min; continue to add 0.500g of initiator benzoyl peroxide (BPO) and mix evenly. Under nitrogen protection, the reaction time lasts for 12 hours to remove the residual monomer as much as possible. Stop the reaction, turn off the water bath and nitrogen, and collect the reactants to obtain.

[0076] Preparation Example 9 In this preparation example, a free radical polymerization method is used to synthesize a polyacrylate pressure-sensitive adhesive.

[0077] Take 70.000g of isooctyl acrylate (2-EHA), 30.000g of methyl acrylate (MA), and 120.000g of ethyl acetate (EA) respectively, add them into a four-necked flask in order according to the mass ratio, install a condensation reflux device, a stirring device and a nitrogen blowing device on the four-necked flask, heat it in a water bath at 85℃, and stir it continuously at 150 r / min; continue to add 0.800g of initiator benzoyl peroxide (BPO) and mix evenly, under nitrogen protection, the reaction time continues for 15h, and the residual monomer is removed as much as possible. Stop the reaction, turn off the water bath and nitrogen, collect the reactants, and obtain.

[0078] Example 1 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 8 is used, and 0.1wt% of itaconic acid (IA), 0.3wt% of TiO2 (Preparation Example 1), and 0.5wt% of COOH-TiO2 (Preparation Example 4) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 400 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0079] Example 2 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 8 is used, and 0.3wt% of itaconic acid (IA), 0.3wt% of TiO2 (Preparation Example 1), and 0.3wt% of COOH-TiO2 (Preparation Example 4) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 400 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0080] Example 3 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 7 is used, and 0.5wt% of itaconic acid (IA), 0.1wt% of TiO2 (Preparation Example 2), and 0.1wt% of COOH-TiO2 (Preparation Example 5) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 300 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0081] Example 4 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 9 is used, and 0.1wt% of itaconic acid (IA), 0.5wt% of TiO2 (Preparation Example 3), and 0.3wt% of COOH-TiO2 (Preparation Example 6) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 500 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0082] Example 5 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 8 is used, and 0.1wt% of itaconic acid (IA) and 0.3wt% of TiO2 (Preparation Example 1) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 400 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0083] Example 6 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 8 is used, and 0.3wt% of itaconic acid (IA) and 0.5wt% of COOH-TiO2 (Preparation Example 4) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 400 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0084] Example 7 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 8 is used, and 0.5wt% of itaconic acid (IA) and 0.1wt% of TiO2 (Preparation Example 2) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 400 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0085] Example 8 In this example, the polyacrylate pressure-sensitive adhesive prepared in Preparation Example 8 is used, and 0.3wt% of itaconic acid (IA) and 0.1wt% of COOH-TiO2 (Preparation Example 5) accounting for the mass of the polyacrylate pressure-sensitive adhesive are respectively added to the polyacrylate pressure-sensitive adhesive, and the stirring rate is adjusted to 400 r / min for mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0086] Example 9 In this example, the polyacrylate composite pressure-sensitive adhesive prepared in Example 1 was mixed with ketoprofen accounting for 2 wt % of the mass of the polyacrylate composite pressure-sensitive adhesive, and the stirring rate was controlled to 400 r / min and the stirring time was 2 h to obtain a drug-carrying layer material.

[0087] The drug-carrying layer material is placed on a release film (anti-sticking layer), left at room temperature for 1 h, then placed in an oven at 50° C., taken out after 15 min, and transferred to a backing film (backing layer) after curing to obtain a ketoprofen transdermal patch.

[0088] Example 10 In this example, the polyacrylate composite pressure-sensitive adhesive prepared in Example 2 was mixed with ketoprofen accounting for 2 wt % of the mass of the polyacrylate composite pressure-sensitive adhesive, and the stirring rate was controlled to 400 r / min and the stirring time was 2 h to obtain a drug-carrying layer material.

[0089] The drug-carrying layer material is placed on a release film (anti-sticking layer), placed at room temperature of 25°C for 1 h, then placed in an oven at 50°C, taken out after being placed for 15 min, and transferred to a backing film (backing layer) after curing to obtain a ketoprofen transdermal patch.

[0090] Embodiment 11 In this example, the polyacrylate composite pressure-sensitive adhesive prepared in Example 3 was added with 1 wt% of ketoprofen, and the mixture was stirred at a rate of 300 r / min for 3 h to obtain a drug-carrying layer material.

[0091] The drug-carrying layer material is placed on a release film (anti-sticking layer), placed at 20° C. for 1.5 hours, then placed in an oven at 45° C., taken out after being placed for 20 minutes, and transferred to a backing film (backing layer) after solidification to obtain a ketoprofen transdermal patch.

[0092] Example 12 In this example, the polyacrylate composite pressure-sensitive adhesive prepared in Example 4 was mixed with 1 wt% of ketoprofen, and the stirring rate was controlled to 500 r / min and the stirring time was 1 h to obtain a drug-carrying layer material.

[0093] The drug-carrying layer material is placed on a release film (anti-sticking layer), placed at 30° C. for 0.5 h, then placed in an oven at 55° C., taken out after being placed for 10 min, and transferred to a backing film (backing layer) after solidification to obtain a ketoprofen transdermal patch.

[0094] Experimental example 1. FTIR spectra of different IA, TiO2, and COOH-TiO2 contents Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (referred to as PSA blank), add different contents of IA (0.1, 0.3, 0.5wt%), adjust the stirring rate to 400 r / min, and perform mechanical blending until the mixture is uniform to obtain the desired composite pressure-sensitive adhesive. The FTIR spectra of pressure-sensitive adhesives with different IA contents are shown in the attached figure. Figure 1 .

[0095] Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (denoted as PSA1), add different contents of TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 1), adjust the stirring rate to 400 r / min and perform mechanical blending until the mixture is uniform to obtain the desired composite pressure-sensitive adhesive. The FTIR spectra of pressure-sensitive adhesives with different TiO2 contents are shown in the attached Figure 2 .

[0096] Take the polyacrylate pressure-sensitive adhesive (denoted as PSA) prepared in the above-mentioned Preparation Example 8, add different contents of COOH-TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 4), adjust the stirring rate to 400 r / min and perform mechanical blending until the mixture is uniform to obtain the desired composite pressure-sensitive adhesive. The FTIR spectra of pressure-sensitive adhesives with different COOH-TiO2 contents are shown in the attached Figure 3 .

[0097] From the above attached Figure 1-3 It can be seen that the polyacrylate pressure-sensitive adhesives with different monomer ratios synthesized in the present invention have a wavelength range of 1600-1450 cm⁻¹ and 1619-1637 cm -1 There is no C=C skeleton vibration peak in the range, indicating that there is no C=C, which indicates that the reaction between the monomers is complete and there is no residual monomer in the system. This indicates that the entire reaction can be carried out completely forward, the monomer conversion rate is high, and the residual monomer is avoided from causing toxicity or affecting biocompatibility. The polyacrylate composite pressure-sensitive adhesive of the present invention provides a basic guarantee for the non-toxicity and good biocompatibility of PSA, and can be used as a patch material for human body.

[0098] 2. Effects of different contents of IA, TiO2, and COOH-TiO2 on the bonding properties of polyacrylate pressure-sensitive adhesives before and after immersion in water This experimental example tests the effects of different contents of IA, TiO2, and COOH-TiO2 on the bonding properties of polyacrylate pressure-sensitive adhesive before and after immersion in water.

[0099] The prepared pressure-sensitive adhesive film was soaked in water for 12 hours and then taken out. The surface moisture was quickly wiped off with filter paper before testing. The specific test indicators include: According to the provisions of the Chinese Pharmacopoeia (2020 edition), the initial adhesion test of the pressure-sensitive adhesive film is carried out using the inclined rolling ball method in accordance with GB4852-84 pressure-sensitive adhesive tape initial adhesion test method. The measurement result is the maximum steel ball number that can be adhered, and the unit of the rolling ball is #; According to the provisions of the Chinese Pharmacopoeia (2020 edition), the test method for the adhesion of pressure-sensitive adhesive tapes in GB4851-84 is used to perform the adhesion test using the hanging weight method. The test results are expressed as the average value of the sample's detachment time (h); According to the provisions of the "Chinese Pharmacopoeia" (2020 edition), the 180° peel strength (N) test of pressure-sensitive tape is carried out using an electronic peel testing machine in accordance with the GB2972-81 pressure-sensitive adhesive tape 180° peel strength test method.

[0100] Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (referred to as blank PSA1), add different contents of IA (0.1, 0.3, 0.5wt%), adjust the stirring rate to 400 r / min, and mechanically blend until the mixture is uniform to obtain the desired composite pressure-sensitive adhesive. The results of the effects of different contents of IA on the pressure-sensitive adhesive before and after immersion in water are shown in the attached Figure 4 And Table 1 below.

[0101] Table 1 Effect of different IA contents on pressure-sensitive adhesive before and after immersion in water

[0102] like Figure 4 As shown in Table 1, with the increase of IA content, the initial adhesion of the film decreases slightly, the sustained adhesion increases significantly, and the 180° peel strength increases first and then decreases. The results show that the bonding performance of the pressure-sensitive adhesive modified by IA is improved to a certain extent and the bonding performance of the film after immersion in water is also within the applicable range.

[0103] Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (referred to as blank PSA1), add different contents of TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 1), adjust the stirring rate to 400 r / min and perform mechanical blending until the mixture is uniform to obtain the desired composite pressure-sensitive adhesive. The results of the effects of different contents of TiO2 on the pressure-sensitive adhesive before and after immersion in water are shown in the attached Figure 5 And Table 2 below.

[0104] Table 2 Effect of different TiO2 contents on pressure-sensitive adhesive before and after immersion in water

[0105] like Figure 5 As shown in Table 2, with the increase of TiO2 content, the maximum adhesion can reach more than 40 h, which is 20 h higher than that of the unmodified pressure-sensitive adhesive. The adhesion after immersion in water is as high as 35 h. It has good water resistance and high peel strength, and the initial adhesion is also within the applicable range.

[0106] Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (referred to as blank PSA1), add different contents of COOH-TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 4), adjust the stirring rate to 400 r / min and perform mechanical blending until the mixture is uniform to obtain the desired composite pressure-sensitive adhesive. The results of the effects of different contents of COOH-TiO2 on the pressure-sensitive adhesive before and after immersion in water are shown in the attached Figure 6 And Table 3 below.

[0107] Table 3 Effect of different contents of COOH-TiO2 on pressure-sensitive adhesive before and after immersion in water

[0108] like Figure 6 As shown in Table 3, with the increase of COOH-TiO2 content, the maximum adhesion can reach more than 40 h, which is 20 h higher than that of the unmodified pressure-sensitive adhesive. The adhesion after immersion in water is as high as 42 h, with good water resistance and high peel strength, and the initial adhesion is also within the applicable range.

[0109] 3. Effect of IA blended with different contents of TiO2 and COOH-TiO2 on the bonding properties of polyacrylate before and after immersion in water This experimental example tests the effects of different contents of IA, TiO2, and COOH-TiO2 blends on the bonding properties of polyacrylate pressure-sensitive adhesive before and after immersion in water. The specific test indicators and methods are the same as those of the aforementioned experimental example 2.

[0110] Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (denoted as PSA1), add 0.3wt% IA and 0.3wt% TiO2 (Preparation Example 1) to blend, and add 0.3wt% IA, 0.3wt% TiO2 (Preparation Example 1) and 0.3wt% COOH-TiO2 (Preparation Example 4) to blend, adjust the stirring rate to 400 r / min for mechanical blending until the mixture is uniform, and obtain the desired composite pressure-sensitive adhesive.

[0111] In this experimental example, the effects of different blending systems on the bonding properties of polyacrylate before and after immersion in water are shown in Table 4 below.

[0112] Table 4 Effect of different blending systems on the bonding properties of polyacrylate before and after immersion in water

[0113] It can be seen that the initial adhesion of the pressure-sensitive adhesive modified by 0.3% (IA+TiO2) blending has a slight increase, the lasting adhesion has increased significantly, and the 180° peel strength has also increased slightly; while the initial adhesion of the pressure-sensitive adhesive modified by 0.3% (IA+COOH-TiO2) blending has a slight increase, the lasting adhesion has increased significantly, and the 180° peel strength has also increased slightly. The lasting adhesion of the pressure-sensitive adhesive modified by 0.3% (IA+TiO2) blending can reach up to 52h, which is 30h higher than that of the unmodified pressure-sensitive adhesive, with good water resistance and high peel strength; the lasting adhesion of the pressure-sensitive adhesive modified by 0.3% (IA+COOH-TiO2) blending can reach up to 64h, which is 40h higher than that of the unmodified pressure-sensitive adhesive, with good water resistance and high peel strength.

[0114] The above results show that the adhesive properties of the pressure-sensitive adhesives modified by blending IA and TiO2 and COOH-TiO2 are improved to varying degrees, and the water resistance is good.

[0115] 4. Effect of different contents of IA, TiO2, and COOH-TiO2 on water absorption of polyacrylate pressure-sensitive adhesive This experimental example tests the effect of different contents of IA, TiO2, and COOH-TiO2 on the water absorption of polyacrylate pressure-sensitive adhesive.

[0116] According to HG / T 3344-2015, the water absorption rate of the pressure-sensitive adhesive sample was measured. The film was cut into 2cm×2cm standard specimens and dried in an oven at 50℃ until constant weight. The weight of the film was accurately weighed and recorded as W2. Then the dried film was placed in a beaker with enough water and placed in an oven at 50℃ for 24 hours. After taking it out, the surface moisture was quickly absorbed with filter paper, and then weighed and recorded as W3.

[0117] The water absorption of the pressure-sensitive adhesive sample was measured: Water absorption (%) = (W3-W2) / W2×100%; Wherein, W2 is the mass (g) of the pressure-sensitive adhesive sample after the solvent is removed, and W3 is the mass (g) of the pressure-sensitive adhesive sample after the surface moisture is removed after being placed in water for 24 h.

[0118] Take the polyacrylate pressure-sensitive adhesive prepared in the above Preparation Example 8, add different contents of IA (0.1, 0.3, 0.5wt%), different contents of TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 1), and different contents of COOH-TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 4), adjust the stirring rate to 400 r / min and perform mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0119] The water absorption test results of pressure-sensitive adhesives with different IA, TiO2 and COOH-TiO2 contents are shown in the attached Figure 7 .

[0120] It can be seen that with the increase of IA content, the water absorption rate of the pressure-sensitive adhesive film gradually decreases, so it can exist stably in a humid environment. Since TiO2 is a hydrophilic substance, the water absorption rate of the pressure-sensitive adhesive film gradually increases with the increase of TiO2 content, which can effectively absorb skin sweat. With the increase of COOH-TiO2 content, the water absorption of the pressure-sensitive adhesive film first decreases and then increases, so it can exist stably in a humid environment. It can be seen that the water absorption rate of the three modified samples is less than 10%, and the stability in a humid environment is relatively high.

[0121] 5. Effect of different contents of IA, TiO2, and COOH-TiO2 on water vapor transmission rate of pressure-sensitive adhesive This experimental example tests the effect of different contents of IA, TiO2, and COOH-TiO2 on the water vapor transmission rate of polyacrylate pressure-sensitive adhesive.

[0122] Place 100 mL of distilled water in a 150 mL beaker and weigh it as W1. Seal the beaker with a film and place it in a dry, 37°C incubator for 24 h. Remove the film and weigh it as W2. Measure the area S of the beaker mouth and calculate the water vapor transmission rate P (g·m -2 ·h -1 ):P=(W1-W2) / 24×S.

[0123] Take the polyacrylate pressure-sensitive adhesive prepared in the above Preparation Example 8, add different contents of IA (0.1, 0.3, 0.5wt%), different contents of TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 1), and different contents of COOH-TiO2 (0.1, 0.3, 0.5wt%, Preparation Example 4), adjust the stirring rate to 400 r / min and perform mechanical blending until the mixture is uniform, to obtain the desired composite pressure-sensitive adhesive.

[0124] The water vapor transmission rate test results of pressure-sensitive adhesives with different IA, TiO2 and COOH-TiO2 contents are shown in the attached Figure 8 .

[0125] It can be seen that the air permeability of the pure polyacrylate pressure-sensitive adhesive matrix is ​​only 2.5 g·m -2 ·h -1 , body fluids are difficult to penetrate the patch. Body fluids gather on the skin surface and are difficult to evaporate, causing the skin to be soaked and white, and even causing allergies or inflammation. The water vapor permeability of the pressure-sensitive adhesive modified with different contents of IA, TiO2, and COOH-TiO2 was significantly improved, among which the water vapor permeability of the pressure-sensitive adhesive film modified with COOH-TiO2 could reach up to 24 g·m -2 ·h -1 The above can absorb sweat on the skin surface normally, and there will be no soaking and whitening during use.

[0126] 6. Effect of different contents of IA, TiO2, and COOH-TiO2 blending modification on water absorption and water vapor transmission rate of polyacrylate pressure-sensitive adhesive This experimental example tests the effects of blending different contents of IA with TiO2 and COOH-TiO2 on the water absorption and water vapor transmission rate of polyacrylate pressure-sensitive adhesive. The specific test indicators and methods are the same as those of the above-mentioned experimental examples 4 and 5.

[0127] Take the polyacrylate pressure-sensitive adhesive prepared in the above-mentioned Preparation Example 8 (denoted as PSA1), add 0.3wt% IA and 0.3wt% TiO2 (Preparation Example 1) to blend, and add 0.3wt% IA, 0.3wt% TiO2 (Preparation Example 1) and 0.3wt% COOH-TiO2 (Preparation Example 4) to blend, adjust the stirring rate to 400 r / min for mechanical blending until the mixture is uniform, and obtain the desired composite pressure-sensitive adhesive.

[0128] In this experimental example, the test results of the effects of different blending systems on the water absorption and water vapor transmission rate of polyacrylate pressure-sensitive adhesive are shown in Table 5 below.

[0129] Table 5 Effect of different blending systems on water absorption and water vapor transmission of pressure-sensitive adhesives

[0130] It can be seen that the water absorption rate of the pressure-sensitive adhesive modified by 0.3% (IA+TiO2) and 0.3% (IA+COOH-TiO2) is increased, which can effectively absorb sweat on the skin surface, and the water absorption rate is less than 10%, and the stability in a humid environment is relatively high. The water vapor transmission rate of the pressure-sensitive adhesive modified by 0.3% (IA+TiO2) and 0.3% (IA+COOH-TiO2) is significantly improved, reaching 33g·m -2 ·h -1 The above can effectively absorb sweat on the skin surface and prevent whitening and swelling during the use of the patch.

[0131] 7. In vitro release of ketoprofen transdermal patch The in vitro release patterns of the prepared patches and commercially available ketoprofen patches were investigated using a constant temperature oscillator. A 1 cm × 1 cm transdermal patch was added to a pretreated dialysis bag, the bag was tied tightly, and placed in a centrifuge tube containing 4 mL of pH 7.4 PBS solution. The oscillator was incubated at 37°C and 100 r·min. -1 Oscillate under the conditions. Take 0.8 mL of samples at 0.5, 1, 2, 4, 6, 8, 10, 12, 24, 36, 48, 60, and 72 h, and replenish the blank release medium with equal volume at the same temperature in time. Take out the solution and filter it through a 0.45 μm microporous membrane, inject the sample for detection, and conduct parallel tests 3 times. Calculate the cumulative release per unit area (Q) at different time points according to the following formula: ; Wherein, V1 is the volume of the release medium, V2 is the volume of each sampling, Cn is the drug concentration measured at the nth sampling, Ci is the concentration of the drug in the release solution at the ith sampling, and A is the permeation area.

[0132] The in vitro release percentage (Pr) was then calculated according to the formula: ; Among them, Qt is the cumulative drug release at different times, and D is the labeled amount.

[0133] Take the polyacrylate pressure-sensitive adhesive (denoted as PSA) prepared in the above-mentioned Preparation Example 8 空白 ), 0.3wt% IA, 0.3wt% TiO2 (Preparation Example 1), 0.3wt% COOH-TiO2 (Preparation Example 4), 0.3wt% IA + 0.3wt% TiO2 (Preparation Example 1), 0.3wt% IA + 0.3wt% COOH-TiO2 (Preparation Example 4) were added respectively, and the stirring rate was adjusted to 400 r / min for mechanical blending until the mixture was uniform, to obtain the desired composite pressure-sensitive adhesive, and a transdermal patch was prepared according to the method in Example 9. At the same time, a general commercially available polyacrylate pressure-sensitive adhesive patch (Ketoprofen patch 7cm*10cm, containing ketoprofen 20mg) was used as a control.

[0134] In this experimental example, the in vitro release percentage curves of each pressure-sensitive adhesive transdermal patch are shown in the attached figure. Fig. 9 It can be seen that ketoprofen is released by 72% within 3 days, which is significantly higher than the commercially available pressure-sensitive adhesive products.

[0135] The cumulative release rate and time of in vitro release were fitted by zero-order kinetic equation, first-order kinetic equation and Higuchi equation respectively to obtain R 2 , and according to R 2 The equation for determining the in vitro release process, R 2 The larger the value, the better the equation fits. The fitting equation for the in vitro release behavior of the modified transdermal patch is shown in Table 6 below.

[0136] Table 6 Fitting equations for in vitro release behavior of transdermal patches

[0137] It can be seen that the first-order kinetic equation for preparing the pressure-sensitive adhesive transdermal patch of the present invention is well fitted, and its R 2 Larger (R 2 The larger the value, the better the equation fits), and the better the clinical application effect.

[0138] It can be seen that by adding an appropriate amount of IA, TiO2 and / or COOH-TiO2 to the polyacrylate pressure-sensitive adhesive of the present invention, the entire composite pressure-sensitive adhesive shows good comprehensive performance in terms of bonding performance, wetting performance, water absorption rate and water vapor permeability, and is suitable for preparing a multifunctional polyacrylate pressure-sensitive adhesive to meet the application requirements in transdermal patches and the like.

[0139] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A polyacrylate composite pressure-sensitive adhesive, characterized in that: It includes a polyacrylate pressure-sensitive adhesive, and a mixture of itaconic acid and inorganic nanoparticles; The inorganic nanoparticles include spherical mesoporous titanium dioxide nanoparticles and / or carboxylated spherical mesoporous titanium dioxide nanoparticles; The itaconic acid is added in an amount of 0.1-0.5 wt % based on the polyacrylate pressure-sensitive adhesive; The inorganic nanoparticles are added in an amount of 0.1-1.0 wt % based on the polyacrylate pressure-sensitive adhesive.

2. The polyacrylate composite pressure-sensitive adhesive according to claim 1, characterized in that: The inorganic nanoparticles include spherical mesoporous titanium dioxide nanoparticles; the spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5wt% based on the polyacrylate pressure-sensitive adhesive; or, The inorganic nanoparticles include carboxylated spherical mesoporous titanium dioxide nanoparticles; the carboxylated spherical mesoporous titanium dioxide nanoparticles are added in an amount of 0.1-0.5wt% based on the polyacrylate pressure-sensitive adhesive; or, The inorganic nanoparticles include a mixture of spherical mesoporous titanium dioxide nanoparticles and carboxylated spherical mesoporous titanium dioxide nanoparticles; the addition amount of the spherical mesoporous titanium dioxide nanoparticles based on the polyacrylate pressure-sensitive adhesive is 0.1-0.5wt%; the addition amount of the carboxylated spherical mesoporous titanium dioxide nanoparticles based on the polyacrylate pressure-sensitive adhesive is 0.1-0.5wt%.

3. The polyacrylate composite pressure-sensitive adhesive according to claim 2, characterized in that: The parameters of the spherical mesoporous titanium dioxide nanoparticles include: specific surface area 200-300m 2 g -1 , average pore size 7-8nm, average pore volume size 0.4-0.5cm 3 g -1 ; The preparation method of the spherical mesoporous titanium dioxide nanoparticles comprises: Tetrabutyl titanate is added to ethylene glycol and mixed, and a mixed solution of acetone and water is added to mix, and the precipitate is collected to obtain ethylene glycol titanium; The titanium glycolate is collected, water is added, and the mixture is heated and refluxed to obtain the desired spherical mesoporous titanium dioxide nanoparticles.

4. The polyacrylate composite pressure-sensitive adhesive according to claim 2, characterized in that: The parameters of the carboxylated spherical mesoporous titanium dioxide nanoparticles include: specific surface area 180-220m 2 .g -1 , average pore size 4.5-5.0nm, average pore volume size 0.2-0.3cm 3 g -1 ; The preparation method of the carboxylated spherical mesoporous titanium dioxide nanoparticles comprises: taking TiO2 powder, adding alkaline solution and mixing, adding sodium chloroacetate and heating to react; collecting the reactants and washing them until they are neutral to obtain the nanoparticles.

5. The polyacrylate composite pressure-sensitive adhesive according to any one of claims 1 to 4, characterized in that: The polyacrylate pressure-sensitive adhesive comprises the following components in parts by weight: Soft monomer 55-70 parts by weight; 30-40 parts by weight of hard monomer; Functional monomer 0-5 parts by weight; Initiator 0.3-0.8 parts by weight; 80-120 parts by weight of solvent.

6. The polyacrylate composite pressure-sensitive adhesive according to claim 5, characterized in that: The soft monomer includes at least one of isooctyl acrylate, 2-ethylhexyl acrylate or n-butyl acrylate; and / or, The hard monomer includes at least one of methyl acrylate, ethyl acrylate, methyl methacrylate or ethyl methacrylate; and / or, The functional monomer includes at least one of hydroxyethyl acrylate and acrylic acid; and / or, The initiator comprises benzoyl peroxide; and / or, The solvent included ethyl acetate.

7. A method for preparing the polyacrylate composite pressure-sensitive adhesive according to any one of claims 1 to 6, characterized in that: The method comprises the steps of blending a selected amount of the polyacrylate pressure-sensitive adhesive with itaconic acid and inorganic nanoparticles.

8. The method for preparing the polyacrylate composite pressure-sensitive adhesive according to claim 7, characterized in that: The method further comprises the step of preparing the polyacrylate pressure-sensitive adhesive, including the step of mixing selected amounts of the soft monomer, hard monomer, functional monomer, initiator and solvent, and performing polymerization reaction under a protective atmosphere.

9. A transdermal patch, characterized in that: It includes a backing layer, a drug-carrying layer and an anti-adhesive layer; The drug-carrying layer comprises a mixture of the polyacrylate composite pressure-sensitive adhesive according to any one of claims 1 to 6 and an active drug; The active drug accounts for 1-3wt% of the mass of the polyacrylate composite pressure-sensitive adhesive.

10. A method for preparing the transdermal patch as claimed in claim 9, characterized in that: The steps include: Taking a selected amount of the polyacrylate composite pressure-sensitive adhesive and mixing it with an active drug; Placing the obtained mixture on the selected anti-sticking layer surface and curing it to form the drug-carrying layer; Take the selected backing layer and compound it to obtain it.

Citation Information

Patent Citations

  • Mesoporous silica modified pressure-sensitive adhesive and application thereof

    CN114106746A

  • Process for preparing poly acrylate composite emulsion for pressure sensitive adhesive

    CN1944480A

  • Preparation method of mesoporous tio2 film using tio2 nanoparticles and graft copolymer and dye sensitized solar cells using the same

    KR1020130110427A